Rat Strain Differences in Susceptibility to Alcohol-Induced Chronic Liver Injury and Hepatic Insulin Resistance - Sarah M. DeNucci; Ming Tong; Lisa Longato; Margot Lawton; Mashiko Setshedi; Rolf I. Carlson; Jack R. Wands; Suzanne M. de la Monte (Gastroenterology Research and Practice)
The finding of more severe steatohepatitis in alcohol fed Long Evans (LE) compared with Sprague Dawley (SD) and Fisher 344 (FS) rats prompted us to determine whether host factors related to alcohol metabolism, inflammation, and insulin/IGF signaling predict proneness to alcohol-mediated liver injury. Adult FS, SD, and LE rats were fed liquid diets containing 0% or 37% (calories) ethanol for 8 weeks. Among controls, LE rats had significantly higher ALT and reduced GAPDH relative to SD and FS rats. Among ethanol-fed rats, despite similar blood alcohol levels, LE rats had more pronounced steatohepatitis and fibrosis, higher levels of ALT, DNA damage, pro-inflammatory cytokines, ADH, ALDH, catalase, GFAP, desmin, and collagen expression, and reduced insulin receptor binding relative to FS rats. Ethanol-exposed SD rats had intermediate degrees of steatohepatitis, increased ALT, ADH and profibrogenesis gene expression, and suppressed insulin receptor binding and GAPDH expression, while pro-inflammatory cytokines were similarly increased as in LE rats. Ethanol feeding in FS rats only reduced IL-6, ALDH1–3, CYP2E1, and GAPDH expression in liver. In conclusion, susceptibility to chronic steatohepatitis may be driven by factors related to efficiency of ethanol metabolism and degree to which ethanol exposure causes hepatic insulin resistance and cytokine activation.